An Efficient Chemo‐Selective N‐Alkylation Methodology for the Structure Diversification of Indolylbenzimidazoles. Issue 11 (17th March 2020) - Barasa, Leonard; Yong, Alison; Yoganathan, Sabesan
Abstract: Indolylbenzimidazoles have emerged as an important pharmacophore during drug discovery efforts. More specifically, N ‐alkylation of indole and/or benzimidazole motifs has been a useful strategy for structure diversification to generate bioactive leads. Herein, we report a simple and efficient methodology for the chemo‐selective N ‐alkylation of indolylbenzimidazole scaffolds. This approach takes advantage of the pKa differences between the indole and benzimidazole nitrogen to achieve the desired chemo‐selectivity. Using the reported method, one can readily access a selection of mono‐ N ‐alkylated or asymmetrically bis‐alkylated indolylbenzimidazole scaffolds in a simple one‐pot operation. Moreover, this method provides the desired products in excellent yield and demonstrates a broad substrate scope. Abstract : N ‐alkylated indolylbenzimidazoles have emerged as an important pharmacophore for drug discovery. However, lack of synthetic methods to access structurally diverse N ‐alkylated derivatives in a simple, economical way limits drug discovery efforts. Herein, we report a highly efficient and chemo‐selective N ‐alkylation of indolylbenzimidazole scaffolds, and with a remarkable substrate scope. Our approach enables researchers to access mono‐ N ‐alkylated or asymmetrically bis‐alkylated indolylbenzimidazole scaffolds in a simple, one‐pot operation, allowing a convenient and economical path to investigate indolylbenzimidazoles for medicinal chemistry efforts.